Physical education, exercise, and sport science in a changing society - Freeman, William Hardin (Burlington, MA : Jones & Bartlett Learning, 2015)
Written for the introductory or foundational course, the eighth edition provides a modern, comprehensive, and balanced entry to the fields of physical education, exercise science, and sport science. This revision outlines the origin and development of these disciplines and looks forward to their application of the latest data and technologies. It identifies current conflicts and includes discussion on the changing focuses of the field and the broader realms it encompasses. The text is organized in an easy to follow format, first defining the profession of exercise science and sport science, then providing an overview of the disciplines that study the cultural, social, and scientific foundations of this profession. In later chapters, the text builds upon that foundation and examines career development and job opportunities, looking at the traditional areas of teaching and coaching, the expanding career options of sport management, and the new world of the technological workplace
What is our field? -- The academic foundations of exercise science and kinesiology -- Physical education and sport in the ancient world -- Physical education and sport in medieval and early modern Europe -- The development of American physical education to 1941 -- The rise of modern sport in the United States and England to 1941 -- American exercise science and sport from 1941 to today -- Philosophy in exercise science and sport -- Ethics and problems in exercise science, physical education, and sport -- Preparing for a career -- Traditional careers in physical education and sport -- Careers in sport, exercise science, kinesiology -- International exercise science and sport today -- Current issues in American exercise science and sport -- Into the future in exercise science and sport
Includes bibliographical references and index
Keywords: Physical education and training; Physical education and training; Physical Education and Training